Peran Unit Penelitian dan Pengembangan (Litbang) Harian Serambi Indonesia Terhadap Sarana Temu Balik Informasi untuk Jurnalis (Jurnal Adabiya, 2020)
This research "The Role of Research Units and Development (R & D) newspaper of Serambi Indonesia towards information seeking behavior for Journalist." this research examine (1) how the role of the research unit and development ( R & D) newspaper of Serambi Indonesia towards information seeking behavior for journalist and to know (2) how was form Information Seeking behavior for journalist on document R & D newspaper of Serambi Indonesia. This research used methods qualitative using Interview and documentation. The results of this research is to show that role R & D newspaper of serambi Indonesia as documentator, supplier data requirements for internal parties and external, provider source information newspaper, compiler news thematic, data supplier for commercial necessity, archiver history newspaper of Serambi Indonesia, and companion content visual. In order to information seeking behavior journalist that is through set document the results coverage journalist, indexation based on title news, date published news, and covering news, accordingly with needs information use, strategy searches have done based on title news, date published, and covering news, browse set documents found, and judgment relevance.